Representações da infância no manual escolar em Portugal - da Conceição Mendes de Castro, Teresa; Manuel do Nascimento Lima Ramos , Rui (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This study falls within the scope of Child Studies and defines its specific area in language studies. It assumes the theoretical and methodological fundamentals of discourse analysis, also considering the influence of related areas. It analyses texts present in textbooks and aims to reveal the images that such texts build of children and childhood, as well as the most relevant linguistic resources associated with such construction.The study concludes that children portrayed in these texts are voiceless and powerless; they are consumers but not co-producers of culture; and the texts instil conservative values aimed at maintaining the social order. It concisely shows the set of most relevant linguistic strategies that the texts use in order to reach their illocutionary goals.